Effective Operations and Maintenance (O&M) practices of vehicles: a case study on LGED - Islam, S.M. Monirul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.